The Extent of Antibiotic Dispensing in Self-Medication Encounters in Sudan: A Simulated Patient Study Focusing on Cefixime Sale - Hamadouk RM; Alshareif EM; Ibrahim OM; Albashair ED; Yousef BA (Integrated Pharmacy Research and Practice, 2023)
Riham M Hamadouk,1,2 Einass M Alshareif,1 Omnia M Ibrahim,3 Esra D Albashair,1 Bashir A Yousef4 1Department of Clinical Pharmacy, Faculty of Pharmacy, University of Khartoum, Khartoum, Sudan; 2Department of Clinical Pharmacy and Pharmacy Practice, Faculty of Pharmacy, Almughtaribeen University, Khartoum, Sudan; 3Faculty of Pharmacy, Al-Neelain University, Khartoum, Sudan; 4Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Khartoum, SudanCorrespondence: Bashir A Yousef, Department of Pharmacology, Faculty of Pharmacy, University of Khartoum, Al-Qasr Ave, Khartoum, 11111, Sudan, Tel +249155662037, Fax +249183780696, Email bashiralsiddiq@gmail.comBackground: Antibiotics play an important role in decreasing morbidity and mortality worldwide. However, inappropriate use of them by patients or healthcare professionals contributes to their resistance rendering them less efficacious. Community pharmacists (CPs) have a significant part in reducing antibiotic resistance. Therefore, this study aimed to investigate the dispensing of antibiotics without prescription in community pharmacies with an emphasis on cefixime dispensing.Methods: A cross-sectional, simulated patient (SP) study was conducted in the Khartoum locality. A total of 238 community pharmacies were randomly chosen using simple random sampling. One scenario of uncomplicated urinary tract infection was designed, and six female pharmacy students who were trained to act as SPs presented the scenario. Descriptive statistics were applied to report the study outcomes.Results: In the 238 pharmacy visits, at least one antibiotic was dispensed without a prescription in 69.3% of the simulated visits. Among the dispensed antibiotics, ciprofloxacin was the most dispensed antibiotic followed by cefixime representing 51.5% and 41.8%, respectively, of total dispensed antibiotics. Cefixime was dispensed as a first choice by CPs in 29% of the visits, and in the rest of the visits, only 37.3% of CPs refused to dispense cefixime after SP demand.Conclusion: The findings revealed a high rate of antibiotics dispensing without prescription by CPs in Khartoum state, and cefixime was obtained with ease before and after the patient’s demand. Urgent corrective actions such as imposing strict regulations, monitoring pharmacists’ practice, and endorsing educational programs for pharmacists are needed to prevent inappropriate antibiotic dispensing practices.Keywords: antibiotics, cefixime, community pharmacists, simulated patient, self-medication